Evaluation Of Rapid Methods For Isolation And Characterization Of Salmonella Serovars Isolated From Raw Poultry And Vegetables - Awang Saleh, Noorzaleha (2003)
Cases of salmonellosis in humans have increased in recent years. Poultry, eggs, meat and dairy products are the most commonly implicated foods in salmonella food infection. The widespread increase in salmonellosis is of major health concern especially in the developing countries. The emergence of S. Typbimurium DTI04 has further worsen the problem because of its known multidrug-resistance. For the past three decades, S. Typbimurium was the most frequently isolated serotype in Malaysia. However, in recent studies S. Weltevreden were reported to be the most predominant serovar present in foods. The present study examines the incidence of salmonellas in poultry and four types of vegetables. However, the main focus of the study is to evaluate different rapid methods for isolation and subsequently characterize the isolates obtained using various molecular typing tools. The vegetables chosen for the study include 'selom' (Oenanthe stolonifera), 'pegaga' (Centella asiatica), 'kesum' (Polygonum minus) and 'kangkong' (Ipomoea aquatica). Three hundred and sixty one Salmonella isolates were isolated from 157 samples of raw poultry and the four types of vegetables. The study demonstrated that recoveries of Salmonella were higher in poultry than in vegetables. Samples enriched in Rappaport Vassiliadis (RV) broth and incubated at 420C gave higher recoveries compared to RV broth at 3JOC, Mannitol Selenite Cysteine broth (SC) at 4rC and 37°C. Selective enrichment in RV broth incubated at 42°C and subsequent plating on Hektoen Enteric Agar (HEK) gave the highest number of Salmonella isolation from poultry and vegetables samples. More Salmonella serotypes were isolated from samples enriched in RV than from SC media while there was no obvious difference among Hektoen Enteric Agar, Rambach Agar, Xylose Lysine Deoxycholate Agar and Bismuth Sulphite Agar used for the recovery of Salmonella spp. The conventional cultural method gave highest recoveries of Salmonella followed by enzyme-linked immunosorbent assay (ELISA) and immunomagnetic separation (lMS). 46.6% (34/73) of poultry and vegetable samples were positive for Salmonella by conventional method, 26% (19/73) by ELISA and 1 7.8% ( 1 9/73) by IMS. Mixed growth of diverse flora was observed on Rambach Agar, Hektoen Enteric Agar, Xylose Lysine Deoxycholate Agar plates from IMS while growth of typical colonies of Salmonella were observed on plates using conventional method.